Digital Economy: Identification and Measurements Problems in Regional Economy - Mirolyubova, Tatyana Vasilievna; Karlina, Tatyana Valeryevna; Nikolaev, Roman Sergeevich (Economy of Regions, 2020)
The transformation of information into a key economic resource is accompanied with a wide dissemination of information technologies. Information and communication technologies (ICT), software products, computers and telecommunication equipment are already integrated into the structure of all economics activities. The intensification of this process over the past decade has generated a great interest of the Russian academia in such phenomena as “digitalization of society” and “digital economy”. In the article, we discuss and define the essence of the phenomenon of «digital economy». Digital technologies, introduced into socio-economic and technological processes, will certainly be involved in the generation of the value added of the final product (service), regardless of its purpose (type of activity and sector of the economy). Although information and communication products belong to the information and communication technology (ICT) sector, each economic activity develops, implements and uses its own solutions in the field of ICT, “digital labour” and “digital capital”, which are not directly analysed and measured. In this regard, there is a need to improve approaches to assessing and measuring the volume of the digital economy at different territorial levels, including regional economies. We propose a methodology for measuring the digital economy at the regional level and test it, using the economic and statistical analysis of data for the Perm region of Russia. We have structured the digital economy in the region and identified the core of ICT, the outer tier of ICT and the digital sector outside of ICT. We have discovered it appropriate to measure the digital economy of a region or a country through a system of indicators: ICT costs, the number and share of employment in the digital economy, the volume and share of digital production in the economy, digital labour force, digital production capacity.